THE INDIVIDUAL STRENGTH OF RURAL WORKER - Mida Mahtum (Journal of Research in Organizational Behaviour, 2023)
This research was conducted with the aim of analyzing the effect of self-esteem and individual adaptability on task performance mediated by work engagement on village apparatus. Respondents in this study amounted to 133 village. Based on the research results, it can be concluded that self-esteem has a positive effect on work engagement. individual adaptability has a positive effect on work engagement. Work engagememt, self-esteem and individual adaptability have a positive effect on task performance. Work engagement mediates the relationship between self-esteem and task performance. Work engagement mediates the relationship between individual adaptability and task performance. The managerial implications that can be drawn from this research are to further improve the Task Performance of village officials, it is necessary to increase self-esteem, individual adaptability and work engagement. support from stakeholders such as the village head, the village consultative body and the community and village empowerment office is needed to support the achievement of good village apparatus performance